2016
DOI: 10.1021/acs.jpcc.5b10597
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Tuning and Room-Temperature Photoluminescence of a Physically Self-Assembled Cu2O Nanocolumn Array

Abstract: The morphology modification of nanostructured materials is of great interest due to controllable and unusual inherent properties in such materials. In this work, growth and morphology evolution of a well-separated Cu2O nanocolumn array is explored by tuning deposition angle and substrate rotation speed in oblique angle deposition (OAD). X-ray diffraction and photoluminescence measurements reveal that crystal quality and optical properties crucially depend on the morphology of the nanostructures. An intense roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The enhanced photocatalytic performance was further evidenced by the charge separation and recombination properties. Photo luminance spectra (excitation @380, and 572nm) and the emission were recorded 420, 572 nm and 616 nm of synthesised photocatalyst (Fig.7a-b), confirmed the recombination properties, the slower radiative recombination presence of Cu species may accelerate the valency and conduction band positions, and trap electrons from the photoexcited electron-hole pairs for higher photocatalytic activity [42][43][44] . holes (h vb + ).…”
Section: Photocatalytic Apap Oxidationsupporting
confidence: 59%
“…The enhanced photocatalytic performance was further evidenced by the charge separation and recombination properties. Photo luminance spectra (excitation @380, and 572nm) and the emission were recorded 420, 572 nm and 616 nm of synthesised photocatalyst (Fig.7a-b), confirmed the recombination properties, the slower radiative recombination presence of Cu species may accelerate the valency and conduction band positions, and trap electrons from the photoexcited electron-hole pairs for higher photocatalytic activity [42][43][44] . holes (h vb + ).…”
Section: Photocatalytic Apap Oxidationsupporting
confidence: 59%
“…Mostly different nano‐ composite materials like rGO‐ Ag nanoparticle, Ag–AgCl/ZnFe 2 O 4 magnetic nanocomposite, Ag@helical chiral TiO 2 nanofibers has been used for the degradation of different endrocrine disruptors. However our aim was to use a single component as photocatalyst as recent research shows fascinating results with respect to synthesis, band gap tuning, field electron emission,, thermal energy conversion, energy storage,, catalyst,, hydrophobic surfaces,, gas adsorbant etc. Some specific examples of photocatalytic removal of E1 and EE2 are given in Table .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Cu 2 O, an intrinsically p ‐ type semiconductor appears as a very fascinating simple oxide material to researchers due to its low band gap of 2.2 eV which makes it a visible light active photocatalyst, easy availability, non‐ toxicity, low cost as well as the ease in tuning the morphology and different crystal orientation. However, photocatalytic degradation ability of Cu 2 O towards endocrine disrupting compounds has remained unexplored till date.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the combined effect of deposition angle and the coexistence of copper oxide phases leads to the (4) blue shift of the absorption edge. I. Mukherjee et al [41] found a similar result for physically selfassembled Cu 2 O nano-column array grown by oblique angle sputter deposition. They explained that the blue shift in nano-columnar structures with high anisotropic crystal orientation could be discussed in terms of the light of Burstein-Moss effect since the loss of charge carriers due to trapping at grain boundaries is expected to be minimized in such structures.…”
Section: Optical Propertiesmentioning
confidence: 65%